Використання аутсорсингу як інструменту зниження трансакційних витрат на підприємстві - Гавкалова, Н. Л. (НТУ "ХПІ", 2014)
У статті розкрито сутність поняття трансакційних витрат в контексті функціонування діяльності підприємств. Досліджено вплив використання аутсорсингу на зниження трансакційних витрат. Проаналізовано переваги та ризики застосування аутсорсингу. Обґрунтовано необхідність впровадження аутсорсингу у діяльність підприємства для зниження рівня трансакційних витрат.

The article is dedicated to a problem of “make or buy decision” based on the analysis of transaction costs level. The author focuses on the study the transaction costs influence on the outsourcing choice in the industrial goods production at manufacturing plants. The essence and nature of transaction costs existence at the economic activities of enterprises have been considered, the approaches that explain the nature of their origin are given. The transaction costs interpretations that have been developed within neoinstitutional theory to establish the research distribution on the macro and micro levels have been analyzed. An important factor of the transaction costs appearance at the industrial goods production is the presence of the following characteristics: specificity of assets, the limited number of industrial goods producers and buyers, which causes the opportunistic behavior of contractors. The methodological approach to qualitative and quantitative risk assessment at the use of outsourcing in industry based on the transaction costs analysis. The necessity of transaction costs optimizing to increase the economic activity efficiency of industrial enterprises has been grounded.
Using of outsourcing as an instrument of transaction costs reducing at the enterprise
Keywords: трансформаційні витрати; ризики аутсорсингу; ресурси; контрагенти; enterprise; transaction costs; transformation costs; outsourcing; risks of outsourcing